Pemanfaatan Residu Biogas dari Limbah Cucian Beras dan Kotoran Sapi sebagai Pupuk Organik Cair untuk Tanaman Bayam Merah (Amaranthus tricolor L) - Veronika Amelia Simbolon; Afrilia Rahmi (FORIKES, 2022)
The amount of waste production continues to increase so it is feared that it can have a negative impact on the environment such as water, soil, air pollution, also causes odors and can be a source of disease. This requires proper handling to reduce the amount of waste production. The purpose of this study was to determine the results of gas pressure from a mixture of rice washing waste and cow dung and to determine the growth of red spinach plants given liquid organic fertilizer resulting from biogas residue from a mixture of rice washing waste and cow dung. This study is an experimental study with a static group comparison design to see the observed parameters, namely the results of stem height, number of leaves, and leaf width of red spinach (Amaranthus tricolor L) after being given treatment with liquid organic fertilizer with 0% concentration of biogas residue (control), 25%, 50%, 75%, and 100% for 28 days. The research object was 30 sticks with a factorial pattern (5 concentrations x 3 repetitions x 2 sticks). The results showed that the concentration that gave the best growth effect on all parameters for 28 days was a concentration of 100% with the highest average value at stem height of 3.01 cm, the highest average value for the number of leaves of 5 leaves and an average value of 5 leaves. The highest average in leaf width is 0.65 cm. The use of liquid organic fertilizer with biogas residue succeeded in increasing the growth of red spinach plants, but the growth of red spinach plants was quite slow so that they did not meet the physical criteria for harvesting. It is hoped that the measurement of nutrients in the planting media and liquid organic fertilizer from biogas residue will be carried out so that the constraints on plant growth are measured, and it is hoped that measurements of concentration variations for different types of plants will be carried out in order to determine the best concentration results from the liquid organic fertilizer used.Keywords: biogas residue; red spinach; rice washing waste ABSTRAK Jumlah produksi limbah yang terus meningkat sehingga dikhawatirkan dapat menimbulkan dampak buruk bagi lingkungan seperti pencemaran air, tanah, udara, juga menimbulkan bau serta dapat menjadi sumber penyakit. Hal ini membutuhkan penanganan yang tepat untuk menurunkan jumlah produksi limbah. Tujuan penelitian ini adalah untuk mengetahui hasil tekanan gas dari campuran limbah cucian beras dan kotoran sapi serta mengetahui pertumbuhan tanaman bayam merah yang diberikan pupuk organik cair hasil residu biogas dari campuran limbah cucian beras dan kotoran sapi. Penelitian ini merupakan penelitian eksperimen dengan desain static group comparison untuk melihat parameter yang diamati yaitu hasil tinggi batang, jumlah daun, dan lebar daun tanaman bayam merah (Amaranthus tricolor L) setelah diberikan perlakuan pupuk organik cair hasil residu biogas konsentrasi 0% (kontrol), 25%, 50%, 75%, dan 100% selama 28 hari. Objek penelitian sebanyak 30 batang dengan pola faktorial (5 konsentrasi x 3 pengulangan x 2 batang). Hasil penelitian menunjukkan bahwa konsentrasi yang memberikan pengaruh pertumbuhan terbaik pada seluruh parameter selama 28 hari adalah konsentrasi 100% dengan nilai rata-rata tertinggi pada tinggi batang yaitu 3,01 cm, nilai rata-rata tertinggi pada jumlah daun sebanyak 5 helai daun dan nilai rata-rata tertinggi pada lebar daun yaitu 0,65 cm. Penggunaan pupuk organik cair residu biogas berhasil meningkatkan pertumbuhan tanaman bayam merah namun pertumbuhan tanaman bayam merah cukup lambat sehingga belum memenuhi kriteria fisik untuk dipanen. Diharapkan dilakukan pengukuran unsur hara pada media tanam dan pupuk organik cair hasil residu biogas agar diketahui kendala pada pertumbuhan tanaman yang diukur, serta diharapkan dilakukan pengukuran variasi konsentrasi untuk jenis tanaman yang berbeda guna mengetahui hasil konsentrasi terbaik dari pupuk organik cair yang digunakan.Kata kunci: residu biogas; bayam merah; limbah cucian beras